WHAT IS ACADEMIC WRITING? (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
This article explores the multi-faceted nature of academic writing, defining its core characteristics, linguistic requirements, and its role as a primary vehicle for knowledge dissemination in higher education. The study emphasizes the transition from informal to formal discourse and analyzes the common challenges faced by researchers. Through a methodological review and comparative data analysis, the research highlights how adherence to structural conventions influences the credibility of scholarly work. The findings suggest that mastery of academic tone and evidencebased argumentation is essential for global academic integration.